Phenomenological Study of Living Qur'an in the Tradition of Death and Reinterpretation of the Younger Generation on the Practice of Khataman Al-Qur'an at Bireuen Cemetery, Aceh - Khodijah, Siti; Monang, Sori (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to examine the tradition of reciting the Qur'an at a funeral as a manifestation of the concept of the Living Qur'an in the socio-cultural context of the Bireuen community in Aceh. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and visual documentation. The research findings show that this tradition is not only understood as a form of respect for the deceased but also as a means to strengthen social solidarity, reinforce Islamic identity, and embody the actualization of Qur'anic values, such as amal jariyah and ukhuwah. However, in the last decade, this tradition has faced challenges from reformist groups who criticize it as a form of heresy, as well as the dynamics of the younger generation who have begun to reinterpret its meaning within the framework of purifying religious teachings. Interpretative Phenomenological Analysis (IPA)-based analysis shows that completing the Qur'an at a funeral expands the realm of the Living Qur'an into the event of death, showing a close relationship between the sacred text, social practices, and the life experiences of the local Muslim community. This study provides a new contribution to enrich the discourse of the Living Qur'an by emphasizing the importance of understanding Qur'anic practices within the framework of contemporary culture and social change